Coherent dynamics of coupled electron and nuclear spin qubits in diamond - Childress, L; Gurudev Dutt, M V; Taylor, J M; Zibrov, A S; Jelezko, F; Wrachtrup, J; Hemmer, P R; Lukin, M D (Science (American Association for the Advancement of Science), 2006)
Understanding and controlling the complex environment of solid-state quantum bits is a central challenge in spintronics and quantum information science. Coherent manipulation of an individual electron spin associated with a nitrogen-vacancy center in diamond was used to gain insight into its local environment. We show that this environment is effectively separated into a set of individual proximal 13C nuclear spins, which are coupled coherently to the electron spin, and the remainder of the 13C nuclear spins, which cause the loss of coherence. The proximal nuclear spins can be addressed and coupled individually because of quantum back-action from the electron, which modifies their energy levels and magnetic moments, effectively distinguishing them from the rest of the nuclei. These results open the door to coherent manipulation of individual isolated nuclear spins in a solid-state environment even at room temperature.